2022
DOI: 10.3390/antiox11010132
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Amyloid-β Oligomer Neurotoxicity by Small Molecules with Antioxidative Properties: Potential for the Prevention of Alzheimer’s Disease Dementia

Abstract: Soluble oligomeric assemblies of amyloid β-protein (Aβ), called Aβ oligomers (AβOs), have been recognized as primary pathogenetic factors in the molecular pathology of Alzheimer’s disease (AD). AβOs exert neurotoxicity and synaptotoxicity and play a critical role in the pathological progression of AD by aggravating oxidative and synaptic disturbances and tau abnormalities. As such, they are important therapeutic targets. From a therapeutic standpoint, it is not only important to clear AβOs or prevent their for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 98 publications
(117 reference statements)
0
9
0
Order By: Relevance
“…Together with the aforementioned link between tau aggregation and protein synthesis disruption, RNA oxidation has been reported to play a role in neurodegeneration. The analysis of oxidized RNA species detected in the brains of Alzheimer’s disease and amyotrophic lateral sclerosis patients revealed significant damage of mRNA and rRNA [ 162 ], which suggests a potentially beneficial antioxidant approach, both pharmacological and nutraceutical, to ameliorate these conditions [ 163 , 164 , 165 , 166 ].…”
Section: Discussionmentioning
confidence: 99%
“…Together with the aforementioned link between tau aggregation and protein synthesis disruption, RNA oxidation has been reported to play a role in neurodegeneration. The analysis of oxidized RNA species detected in the brains of Alzheimer’s disease and amyotrophic lateral sclerosis patients revealed significant damage of mRNA and rRNA [ 162 ], which suggests a potentially beneficial antioxidant approach, both pharmacological and nutraceutical, to ameliorate these conditions [ 163 , 164 , 165 , 166 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the small molecules capable of reducing AβO-mediated toxicity highlighted in my previous review were the natural compounds tyrosol, honokiol, and rhynchophylline (Rhy). Notably, almost all of these molecules have potent antioxidative activity, underscoring the central role of oxidative stress in the pathophysiological cascade of AβO toxicity, as described above [17]. In reviewing the signaling pathways involved in the AβO toxicityreducing activity of these molecules, it became apparent that most of these molecules have the capacity to activate the Nrf2 pathway and initiate antioxidant defense responses.…”
Section: Small Molecules With Aβo Toxicity-reducing Activitymentioning
confidence: 96%
“…In addition to these approaches, reducing the intrinsic toxicity of AβOs using certain small molecules is also a potential strategy. Indeed, a number of recent preclinical studies have suggested the viability of this latter approach [17]. Since Aβ accumulation has reached a substantial level by the prodromal stage of AD, it is particularly important to start therapeutic intervention as early as possible to prevent the clinical progression to AD dementia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the review articles, three of them focused on the involvement of oxidative stress in eye disorders, such as vitreoretinal diseases [ 8 ], diseases associated with retinal ganglion cells degeneration [ 9 ] and on the role of bisretinoids of the retina in photo-oxidation, iron-catalyzed oxidation and disease consequences [ 10 ]. The other four review papers summarized the major causes of central nervous system (CNS) redox homeostasis imbalance [ 11 ], the significance of amyloid β-protein oligomers (AβOs) and oxidative stress in AD [ 12 ], the role of TRAP1 in oxidative stress and neurodegeneration [ 7 ] and how PON2 controls oxidative stress, inhibits apoptosis and contributes to the progression of various types of malignancies [ 13 ].…”
mentioning
confidence: 99%